HIDROLISIS ASAM KLORIDA TEPUNG PATI SINGKONG (Manihot esculenta Crantz) DALAM PEMBUATAN GULA CAIR - RTM. Sutamihardja; Srikandi Srikandi; Dian Purnamasari Herdiani (JURNAL SAINS NATURAL, 2015)
Chloride Acid Hydrolysis of Cassava (Manihot esculenta Crantz) Strach Flour in Producing a Liquid Sugar         Cassava (Manihot esculenta Crantz), known as cassava or manioc is a tuber or root of a tree that long with a diameter average of 5-10 cm and a length of 50-80 cm, depending on the type of cassava. Cassava is agricultural products that having high potency source of carbohydrates for food and industrial materials. Cassava starch can be made for liquid sugar by the method of acid hydrolysis using hydrochloric acid. The research results showed that  rendemen at a HCl concentration of 0.75 N and hydrolysis time of 90 minutes was 80.51%. The higest rendemen of liquid sugar at a concentration of 0.5 N HCl and the hydrolysis time of 90 minutes was 84.22%. Results of the analysis indicate liquid sugar content of 16.22% moisture, ash content of 1.46%, 2.16% protein content, fat content of 0.53%, carbohydrates of 63.90%, and a negative starch content.Key words: Cassava,  Flour Cassava Starch, Acid  Hydrolysis, Liquid Sugar ABSTRAK         Singkong (Manihot esculenta Crantz) yang dikenal sebagai ketela pohon atau ubi kayu merupakan umbi atau akar pohon yang rata-rata berdiameter 5-10 cm dan panjang 50-80 cm, tergantung dari jenis singkong. Singkong merupakan hasil produk pertanian yang potensinya tinggi sebagai sumber karbohidrat untuk bahan pangan dan industri. Pati singkong dapat dibuat gula cair dengan metode hidrolisis asam menggunakan asam klorida. Hasil penelitian menunjukkan bahwa nilai rendemen tertinggi pada konsentrasi HCl 0,75 N dan waktu hidrolisis 90 menit yaitu sebesar 80,51%.  Rendemen tertinggi kadar gula pereduksi dari pembuatan gula cair dengan konsentrasi HCl 0,5 N dan waktu hidrolisis 90 menit sebesar 84,22%. Hasil analisa gula cair menunjukkan kandungan kadar air 16,22%, kadar abu 1,46%, kadar protein 2,16%, kadar lemak 0,53% , karbohidrat 63,90%, dan kandungan pati negatif.Kata kunci: Singkong, Tepung Pati Singkong, Hidrolisis Asam, Gula Cair